Pengaruh Bimbingan Islami terhadap Inferiority Feeling Anak Pinggiran di LSM Pemberdayaan Perempuan dan Anak Pinggiran (PPAP) Seroja - Ristiana, Evi; Fadilah, Galih Fajar (Transformatif : Jurnal Pengabdian Masyarakat, 2020)
Islamic guidance based on the Al-Qur'an and Hadith can make a person control inferiority feelings in order to accept himself completely, have confidence in his abilities, and be confident in the work he does. Islamic guidance makes humans behave healthy and can control their deviant behavior. Because with religion and faith make a better person. The purpose of this devotion is to find out whether Islamic guidance has an effect on the inferiority feeling of marginal children in the NGO PPAP Seroja Jebres Surakarta. The population in this study were the peripheral children in the PPAP Seroja Jebres NGO Surakarta. The sample in this study amounted to 15 people with random sampling technique. The results show that there is a significant influence between Islamic guidance variables and inferiority feeling. The contribution of the influence of Islamic guidance on inferiority feeling is quite large